Pelatihan Pemanfaatan Media Augmented Reality Dalam Pembelajaran Qawa’id Rasmi Al-Imla’ Untuk Meningkatkan Ketepatan Menulis Bahasa Arab Mahasiswa - Raudatussolihah, Baiq; Fathurrahman, Ali; Kholida, Masita Taufiqi; Rais. TM, Ahmad; Jamal, Mardhiana (LPPM UNIVERSITAS NAHDLATUL WATHAN MATARAM, 2026)
Abstract: Students' Arabic writing skills still face various obstacles, particularly in the application of the rules of formal pronunciation (qawa'id al-imla') such as the writing of hamzah, alif layyinah, and unpronounced letters. This problem is caused by learning methods that are still conventional and do not utilize interactive media. This community service activity aims to improve the accuracy of students' Arabic writing through training in the use of Augmented Reality (AR) media. The implementation method includes the stages of identifying needs, training in the use of AR media, AR-based learning practices, and intensive mentoring. The results of the activity showed an increase in students' understanding and accuracy of writing, marked by a reduction in errors in aspects of the rules of imla'. In addition, students showed a positive response to the use of AR media, which was considered more interesting, interactive, and facilitated the understanding of abstract concepts. Thus, the use of AR media in imla' learning has proven effective as an innovation in improving the quality of Arabic language learning.